PENGARUH INDEPENDENSI DEWAN PENGAWAS SYARIAH DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE UNTUK MENINGKATKAN KINERJA BMT - Iin Emy Prastiwi (ITB AAS INDONESIA Surakarta, 2017)
This study aims at determining the contribution of the independence Sharia Supervisory Board and Good Corporate Governance individually and simultaneously to the performance of the BMT in Sukoharjo and Karanganyar. This study was a survey research with a quantitative approach. The populations in this study were the manager and supervisor of BMT. The sampling technique was a convenience sampling method possible. Samples taken as many as 30 data were spread at 9 BMT in Sukoharjo, and 6 BMT in Karanganyar. Data were taken by using a questionnaire and the analysis of the balance sheet and profit and loss. Testing of instruments used validity test, reliability test, test of sub-structures I, II, and III and then are analyzed by Path Analysis. The results in this study are: (1) the independency of the Sharia Supervisory Board affects significantly positive on the Good Corporate Governance of 65.4%. (2) the independence of the Sharia Supervisory Board affects significantly negative on the performance of 0,244, (3) Good Corporate Governance affects significantly positive on the performance of 1,125. (4) The independency of the Sharia Supervisory Board and Good Corporate Governance affect significantly positive on the performance of 88.1%.